Rehabilitasi Pantai Berlumpur Dengan Pegar Geobag Rangka Bambu Di Desa Sriwulan Kabupaten Demak - Muhamad Reza Robby Nugraha; Raden Indra Anggun Gemilang (JURNAL TEKNIK HIDRAULIK, 2017)
Coastal erosion, tidal flooding, and land subsidence on the Northern Coast of Central Java, especially on Demak Regency,Sriwulan District have resulted in environmental degradation and coastal retreat. In effort to restore and protect nearly submerged coastal area, through the Building with Nature Project,  Research Center for Water Resources recommends the application of a Low Crested Breakwaters (LCB) structure with bamboo frame as a protective and sediment catcher structure. Prior to the field applied, a numerical model test was performed to see the hydro-oceanographic and morphological response around the structure. Numerical modeling is done using MIKE21 software by creating three model scenarios, LCB with length 75 meters, 500 meters, and 1000 meters. LCB with a length of 75 meters is the LCB to be installed in Sriwulan district while LCB 500 meters and 1000 meters are used to see the spread of sediments If using LCB that longer and has a gap. The results of the numerical model test show that LCB is capable to reduce wave energy, with wave height behind structure reaching 0.04 meters when low tide condition and 0.07 meters during high tide condition. Model simulation results for 5 years showe three LCB sizes with length 75, 500, and 1000 meters for sedimentation behind LCB of 25 cm. The results of monitoring on the performance of PEGAR Geobag prototype in Sriwulan Beach in May 2017 resulted in sediment between 15 cm-25 cm.